Histopathologic tumor regression grading in patients with gastric carcinoma submitted to neoadjuvant treatment: results of a Delphi survey - Tsekrekos, Andrianos; Detlefsen, Sönke; Riddell, Robert; Conner, James; Mastracci, Luca; Sheahan, Kieran; Shetye, Jayant; Lundell, Lars; Vieth, Michael (Human Pathology, 2019)
Studies investigating the histopathologic response of gastric carcinoma to neoadjuvant treatment have used a variety of different tumor regression grading systems. The aim of this Delphi survey was to review the available systems and reach consensus on a potential international standard. An international e-mail–based Delphi survey involving 6 expert pathologists was undertaken between January and October 2017. A questionnaire consisting of 72 items was formed after reviewing the 5 available systems. Rating of the items was done on a symmetric 4-point Likert-type scale, and feedback was provided between rounds. A total of 4 rounds were required to reach consensus on 97% of the items covering the topics: (1) specimen processing, (2) gross examination, (3) cross sectioning/method of sampling, (4) staining, (5) immunohistochemistry, (6) assessment of tumor regression in response to neoadjuvant therapy, (7) tumor regression grading, (8) assessment of regression of nodal metastases, and (9) role of histologic tumor type. Through the outcome of this comprehensive Delphi study, a group of experts is proposing a 4-tiered system for the grading of regression of the primary tumor, combined with a 3-tiered system for lymph node metastases. Grade 1 represents complete response, grade 2 contains less than 10% residual tumor (subtotal regression), grade 3 contains 10% to 50% residual tumor (partial regression), and grade 4 contains greater than 50% residual tumor (minimal/no regression). The addition of “a” “b” or “c” indicates complete, partial, or no response of lymph node metastases. It is recommended to use this grading system irrespective of histologic subtype.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Consensus; Delphi; Gastric cancer; Histopathologic tumor regression grade; Neoadjuvant treatment